ANALISIS PENGARUH RETURN ON ASSETS (ROA), RETURN ON EQUITY (ROE) DAN EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM (Studi Kasus Pada Perusahaan Yang Terdaftar di Jakarta Islamic Index Tahun 2017-2020) - Adhista Setyarini (Media Akuntansi, 2022)
This research aims to analyze Return On Assets (ROA), Return On Equity (ROE) and Earning Per Share (EPS) influence towards stock prices in the group Jakarta Islamic Index period of 2017-2020. in Indonesia Approach used in this research is quantitative research approach (using data that can be measured in a scale of numeric/numbers), using secondary data in the form of panel data (pooling of data) that combines data coherently time (time series) data and kerat latitude (cros section) in that period of time. In analyzing the data, researchers using regression test with the help of eviews application 9. The results showed ROE and EPS effect positive and significant against stock prices. ROA has a positive and insignificant relationship towards stock prices in the group Jakarta Islamic Index period of 2017-2020.